2000
DOI: 10.7589/0090-3558-36.1.86
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Bait for Oral Delivery of Biological Agents to Raccoons and Feral Swine

Abstract: A field study was conducted on Ossabaw Island (Georgia, USA) in March 1994 to evaluate four different types of bait for delivering orally effective biological agents to raccoons (Procyon lotor) and feral swine (Sus scrofa). A deep-fried corndog batter bait, which was previously shown to be ingested by both captive and free-ranging raccoons, and a polymer fishmeal bait which had been shown effective for both raccoons and feral swine were compared with a grain-based dog food meal polymer bait topically coated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…Additional repellents against nontarget animals, such as putrescent whole egg solids or naphthalene-based products, also should be evaluated. The use of generic grain-based baits with an overcoat of species-specific attractant also has been suggested as a plausible means of orally delivering pharmaceuticals to feral swine (Kavanaugh and Linhart, 2000). This approach would require such attractants to be identified, and it highlights an additional area of needed research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional repellents against nontarget animals, such as putrescent whole egg solids or naphthalene-based products, also should be evaluated. The use of generic grain-based baits with an overcoat of species-specific attractant also has been suggested as a plausible means of orally delivering pharmaceuticals to feral swine (Kavanaugh and Linhart, 2000). This approach would require such attractants to be identified, and it highlights an additional area of needed research.…”
Section: Discussionmentioning
confidence: 99%
“…Removal rates (standardized for visitation, following Kavanaugh and Linhart, 2000) were compared among the four treatments in species with $30 cumulative visits by using the chi-square statistic with Yates correction (Alder and Roessler, 1977). For trial 2, we considered the number of baits removed by feral swine versus the total removed for each replicate as the response variable.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike fish meal polymer baits, polymer baits made of dog food meal had little apparent odor and as originally envisioned (Kavanaugh and Linhart, 2000), they were surface-coated with various candidate and proprietary attractants aimed at enhancing discovery and ingestion by target species. Attractants were applied by mixing, dissolving, or suspending them, usually at a 5:95% attractant/wax concentration, in melted wax and then dipping the dog food polymer baits into the melted mixture.…”
Section: Bait Formulationmentioning
confidence: 99%
“…yet, conflicting outcomes exist across published results. Some studies have found that Raccoons do not exhibit a preferential response to certain attractants (i.e., scents or bait; nottingham et al 1989;Kavanaugh and Linhart 2000), while others report that Raccoons respond frequently to specific food scents and bait, such as fruit (campbell and Long 2008) or fish (campbell and Long 2007). These latter studies suggest that perhaps the food scent we employed (crayfish oil) was not preferentially attractive enough.…”
Section: Discussionmentioning
confidence: 99%